A new approach to robust inference in cointegration - JIN, Sainan (Institutional Knowledge at Singapore Management University, 2005)
A new approach to robust testing in cointegrated systems is proposed using non-parametric HAC estimators without truncation. While such HAC estimates are inconsistent, they still produce asymptotically pivotal tests and, as in conventional regression settings, can improve testing and inference.